Kritik terhadap Gaya Arsitektur Masjid Pasujudan Ayodya Sekaran Semarang - Ahmala Husna; Nabila Choirunnisa (Misterius : Publikasi Ilmu Seni dan Desain Komunikasi Visual., 2025)
Each architectural style reflects the prevailing culture, technology, and social needs of its time, and is an important component of the building's image. Architectural style refers to the design characteristics, forms, elements, and aesthetics used to create a building. This research aims to find out the details of the architectural style and its implementation of the Pasujudan Ayodya Mosque building. The research method used is qualitative and data analysis includes observation through literature studies, visual documentation, and analysis of modern architectural theory and its application. The Pasujudan Mosque in Semarang applies the basic principles of art and architecture, referring to the arrangement of elements that harmonize with each other, balance, aesthetics, and materialization. Modern architecture influences the design of the mosque, combining elements of modern architecture with traditional Islamic design.